Evaluation of football players' actions in individual risky situations of offensive play as a model determinant of a sports game - Duda, H. (Journal of Kinesiology and Exercise Sciences, 2020)
The essence of effective training in a sports game is the use of means and forms of teaching in the organisation of a game, which most faithfully reflect the environment of the player's actual activity in natural conditions. Thus, there is a need to accurately identify the conditions of competition in a sports game. One of the types of such activities is observation, which being an elementary method of cognition, based on deliberate, targeted and intended as well as systematic perception of the studied subject, process or phenomenon. Research objective and questions The aim of the work is to assess the level of absolutely dependent cooperation (synergy) during a team sports game in changing game situations, in achieving the highest offensive objective, i.e. scoring a goal. - Is the effectiveness of achieving the highest objective of the game in offensive actions (i.e. scoring a goal) dependent on the level of player synergy? - Is the size of the conflict in the sports objective of the game dependent on creative player involvement? Material and test method - In the work, detailed observation was carried out with regard to players' actions in achieving the highest objective of the game, i.e. scoring a goal. The observation concerned analysis of 134 goals scored in 61 UEFA Champions League and European League football matches in 2009-2020. - In this study, the method of observation was used, with the possibility of repeatedly observing events being the subject of research. - In the research analysis, the use of film material of recorded games on a DVD was taken into account, where the observed effects were applied to an observation sheet. - The situations in which goals were scored and the research material comprised teams that competed in a given match. - The observation of scoring goals took the type of situation and level of interaction between players into account. Results Analysis of the obtained results can be inferred: 1. In achieving the highest objective of offensive actions, a high level of synergy prevails, requiring anticipation of events. 2. The high level of synergistic activities increases with the difficulty of situational tasks. 3. Due to the multi-faceted nature of team games, the player's training process should also affect his/her mental sphere.